Seeking Substantive Justice: The Progressive Spirit of Law on Sexual Violence Crimes - Nurhayati Nurhayati; Ana Fauzia; Fathul Hamdani; Nurhayati binti Abdul Ghani (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Sexual violence is a massive phenomenon that occurs in society. Sexual violence occurs in various places in Indonesia, including educational institutions. Massive sexual violence made the government and the House of Representatives (Dewan Perwakilan Rakyat or DPR) pass the Law on Sexual Violence Crimes (Indonesian: Undang-Undang Tindak Pidana Kekerasan Seksual, abbreviated as TPKS Law). The TPKS Law is oriented as an effort to prevent and overcome criminal acts of sexual harassment. This study aims to analyze the progressive orientation of the TPKS Law, including how the TPKS Law can provide and present substantive justice in society. This research is normative legal research that seeks to discuss and analyze legal products in the form of laws. The approach in this research is a conceptual approach and a statutory approach. The results of the study confirm that the TPKS Law is a law with a responsive character in the form of a progressive orientation related to preventive approaches to prevent sexual violence and the need for policies and mechanisms in each institution to prevent as well as crack down on sexual violence, the need for regular socialization and understanding of sexual violence in each institution, community, transparent, consistent, and conscientious enforcement of criminal law related to sexual violence, and the need for other mechanisms related to efforts to ensure healing and fulfillment of rights for victims of sexual violence.